Case Report: Surgical thrombectomy in a patient with isolated cortical vein thrombosis previously misdiagnosed as brain tumor - Bai, Yang; Dong, Liansheng; Yu, Chunyong; Feng, Sizhe; Liang, Guobiao (Frontiers in Oncology, 2022)
ABSTRACT Introduction: As a rare type of cerebral venous thrombosis, isolated cortical vein thrombosis (ICVT) is easily misdiagnosed as brain tumor, especially in the cases with prominent signs of parenchymal brain lesions. Despite controversy concerning the efficacy and safety, anticoagulant treatment dominates in current therapeutic strategies for ICVT. As yet, surgical thrombectomy in the treatment of ICVT has not been reported. We present hereafter a female with ICVT previously misdiagnosed as brain tumor who had successful surgical thrombectomy. Case Description: A 54-year-old female with progressive left-sided limb weakness suddenly developed focal tonic-clonic epileptic seizure. Physical examination indicated strength of 0/5 in the left limbs. Magnetic resonance imaging (MRI) showed an irregular juxtacortical lesion surrounded with massive edema in the frontoparietal cortex, which was initially diagnosed as glioma. However, it turned out to be ICVT of the central sulcus vein during craniotomy. Then, venotomy and thrombectomy were performed, with instant recanalization of the vein noticed during surgery. In retrospect, we identified the suspected ICVT of the central sulcus vein in preoperative magnetic resonance venotography (MRV) and contrast MRI images. Laboratory tests also revealed homocysteinemia and hypercoagulable states in the patient. Follow-up MRV obtained 3 months after discharge showed cortical vein recanalization. At the one-year follow-up, she exhibited subtle sequelae of weakness in the left lower limb with a modified Rankin scale score of 1. Discussion: Physicians should be aware of ICVT in the differential diagnoses in patients with risk factors, classical symptoms, and parenchymal brain lesions in or near cortex. Surgical thrombectomy excels at realizing definite recanalization and avoiding systematic complications of anticoagulation. It might be a therapeutic alternative for ICVT, especially when craniotomy is performed for treating intracranial hypertension or a definite diagnosis is made during craniotomy.